Attempts to regulate the circulation of foreign currency in Russian Far East Anti–Bolshevik Power in 1919 - A. L. Kiselev (Омский научный вестник: Серия "Общество. История. Современность")
Based on the analysis of the identified sources, the article examines the measures taken by the anti-Bolshevik authorities to regulate the circulation of foreign currency in the Russian Far East in 1919 in the context of historical events of the Civil War and intervention. The theoretical basis of the research is such methods of historical research as historical-genetic, historical-comparative methods, as well as the method of content analysis. Attempts to counter the currency dominance of the money market of the Russian Far East are described, the reasons for the failures of these measures of the white authorities are indicated.